Review paperTrichosporon sp. – pathogenicity, diagnostics and treatment - Rup, Elżbieta; Skóra, Magdalena; Macura, Anna B. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Trichosporon spp. are anamorphic yeast-like fungi widely distributed in the natural environment. They may be isolated from soil and water and can occasionally belong to the human and animal microbiota. In humans, Trichosporon is mainly found on the skin, mucous membranes and nails. The fungus is the causative agent of benign superficial infections but it may also cause serious deep mycoses. Systemic trichosporonosis concerns mainly immunocompromised patients and has a high mortality rate, ranging from 80 to 100%. Difficulties in identification of different species as well as the lack of standardized sensitivity tests in vitro contribute to the limited knowledge available on epidemiology, diagnosis and therapy of Trichosporon infections